Factors associated with mosquito nest eradication behavior for DHF in Boyolali Regency in 2023 - Rosmawati, Elly; Kuncoro, Teguh Tri; Indriani, Citra; Ahmad, Riris Andono (Universitas Gadjah Mada, 2024)
Purpose: DHF cases in Boyolali Regency have experienced an increase in cases over the last four years, and this has been accompanied by a decrease in the ABJ index by 89%, which is an indicator of the success of the Mosquito Nest Eradication (PSN) program. This research aims to identify factors that influence PSN behavior in society. Method: This research uses an observational analytical study design with a cross-sectional approach. Data was collected from 331 respondents in 30 cluster analyses, namely univariate, bivariate, and multivariate, using logistic regression. Results: 331 respondents were found to have good PSN behavior (59.8%). The results of the multivariate analysis showed that the influencing factors were high education level (aOR 2.80; 95%CI 1.31–6.00; p-value 0.008) and region of residence, live in urban areas (aOR 0.42; 95%CI 0.26-069; p-value <0.001), have good knowledge (aOR 1.67; 95%CI 1.01-2.76; p-value <0.042), and have a good attitude (aOR 1.75; 95%CI 1.07-2.86; p-value <0.025). Conclusion: Factors influencing PSN behavior in Boyolali Regency include education level, place of living, attitudes, and knowledge.